Development of saliva-based cTnI point-of-care test: a feasibility study. (25th November 2020) - Westreich, R; Neumann, Y; Deutsch, O; Krief, G; Stiubea-Choen, R; Zager, D
Abstract: Background: Cardiac troponin is the biomarker of choice for detection of myocardial injury. There is a great need for simple point of care troponin testing among patients with chest pain, mainly in the prehospital setting. In this preliminary study we evaluate the feasibility of a novel, saliva-based cTn test. Aim: 1) To evaluate the presence of cTnI in saliva of patients with myocardial injury. 2) To explore the feasibility a saliva-based point-of-care cTn assay. Methods: Saliva samples were collected from 32 patients with myocardial injury who tested positive for conventional cTnT blood tests, and from 13 healthy volunteers. 25 and 9 of these samples, respectively, were subjected to a series of advanced saliva processing procedures: "Amplification buffer" – A unique and complex composition which removes a broad spectrum of saliva inhibiting elements of physical, chemical and biological nature. "Hampering remover" – A device which specifically removes salivary alpha amylase that constitutes ∼50% of the total saliva protein content and therefore increases the detection sensitivity of less concentrated components. "Saliva Concentrator Cartridge" – based on the principles of solid phase extraction cartridges and allows rapid and easy analytes concentration. Processed and unprocessed samples were tested with blood cTnI RDT (Troponin I Rapid Test. specifications: detection limit 1ng/mL of whole-blood; Sensitivity: 95.8%; Specificity: 99.7%). Results were interpreted independently by two investigators and only concordant readouts were included in the analyses. Results were compared to blood cTnT levels Results: Among the 25 positive samples subjected to advanced saliva processing procedures, 21 were confirmed positive by both investigators (sensitivities of 84%). All 4 negative saliva samples were obtained from patients with relatively low blood cTnT levels of 155 ng/L or less. Testing untreated samples, only 2 out of 32 were positive (sensitivities of 6.25%). In both processed and unprocessed samples no false positive results were seen among healthy individuals (0 out of 9 and 0 out of 13, respectively), corresponding to a specificity of 100% for both processed and unprocessed groups. The negative predictive values for processed and unprocessed groups were 69.23% and 30.23 respectively. Statistical accuracies were 88.24% for the processed group and 33.33% for the unprocessed group. Conclusion: This preliminary work demonstrates for the first time the presence of cTnI in saliva of patients with myocardial injury and possible detection of cTnI in clinical saliva samples utilizing a commercial blood-RDT platform. Further research is needed to determine the time activity of troponin in saliva as well as its sensitivity and specificity for myocardial injury. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Salignostics LTD